TINJAUAN YURIDIS NORMATIF TINDAK PIDANA PENGANIAYAAN TERHADAP ANAK DALAM SISTEM PERADILAN PIDANA - M. Rudi Hartono (Universitas Batanghari Jambi, 2015)
Problems criminal acts of child abuse in public life have a major enough in the subject of official and the ordinary people, both under discussion among scientists, law enforcement, crime analysts and the public in general. Indeed even so, the perceived need for a specific discussion on this issue. With contribute ideas in order to understanding the problems of violence such as child abuse even further to provide input for future crime prevention efforts.A particularly violent acts such as torture committed against children as victims, when viewed from the positive aspects of the Indonesian criminal law, then such actions can be categorized as a criminal offense, because the positive Indonesian criminal law in addition to regulating the inter-individual interests also with the state as an institution that has function to protect every citizen, in this case someone who has been the victim of a crime. Basically to determine a person has committed a crime or not, it must meet the elements of a criminal offense, with the actions undertaken are prohibited by law and offenders who commit these crimes are held to criminal liability under criminal law.Keyword : Crime, Children and Criminal Justice System